AstrolÃbio: um corpus de redaÃÃes escolares do CearÃ anotado multidimensionalmente conforme a TEI P5 - Katiuscia de Moraes Andrade (2013)
AstrolÃbio is a compiled corpus, with multidimensional annotation, and shared under Creative Commons Attribution-NonCommercial 3.0 Unported licence. It is a corpus, in Brazilian Portuguese, that uses advanced technologies to text processing and corpora annotation. AstrolÃbio has multidimensional annotation based on TEI P5 guidelines, that prescribes XML metalanguage. Through these guidelines, essential structures from the annotated documents were preserved, keeping the transcription as reliable as possible to the original. By using tag <choice>, it enabled keep, in the same archive, linguistic variation phenomena, orthographic and punctuation errors, as the respectives corrected and normalized forms, and also makes possible the visualization of added and deleted terms. To automatize the integration of many levels of annotation, Astro was used, it is a software that works with several Python modules to Natural Language Processing (NLP), including Aelius and Enchant. To POS tagging, Aelius, a package that uses Natural Language Toolkit (NLTK) libraries, was utilized. From Aelius, AeliusHunPosMacMorpho was chosen, it is a tagger based on HunPos and trained by MAC-Morpho, a corpus composed of journalistic texts. The 9spell checking was made by Enchant, a large library with API (Application Programming Interface) in C and C++ languages. The tagger chosen from inside training corpus MacMorpho,. AstrolÃbio's texts were produced during text production workshops from the second edition of Rota das Especiarias project, realized on first semester of 2012, with public school students from Camocim, Barroquinha e Jijoca de Jericoacoara, cities located in CearÃ. Until this moment of AstrolÃbio's creation, concluded stages are texts selection, compilation and the first step of automatic annotation by Astro. AstrolÃbio corpus is already partially avaiable at Rota das Especiarias' website (www.rotadasespeciarias.art.br). Soon, the corpus will be submitted to University of Oxford Text Archive (OTA). As we observed from corpora scene of Portuguese, there's no corpus, in Brazilian Portuguese, with this level of annotation.